2016
DOI: 10.1186/s13099-016-0092-6
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and molecular characterization of Mycobacterium avium subsp. paratuberculosis in Shandong province, China

Abstract: BackgroundMycobacterium avium subspecies paratuberculosis (Map) causes Johne’s disease in domestic and wild ruminants. It has been a debate that whether Map can cause Crohn’s disease in human. To our knowledge there is no report about molecular characterization of Map in China, although several Map strains have been reported in other country. The objectives of this study was to know the recent prevalence of Johne’s disease in dairy farms in Shandong province, and have a better understanding of genotypic distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…In the late stage of the disease, cows became extremely thin and milk production declines sharply. In this study, the identified MAP strain was type C (dairy cattle), consistent with Yue et al's previous research [18]. It indicates that type C is the predominant type in cattle in Shandong Province, China.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the late stage of the disease, cows became extremely thin and milk production declines sharply. In this study, the identified MAP strain was type C (dairy cattle), consistent with Yue et al's previous research [18]. It indicates that type C is the predominant type in cattle in Shandong Province, China.…”
Section: Discussionsupporting
confidence: 91%
“…The seroprevalence investigation indicated that 66.7% (6/9) of herds and 14.2% of animals were positive for MAP antibodies, which is higher than the findings from previous studies from Shandong [18] and other provinces in China [41][42][43][44]. These studies recorded MAP antibodies in 2.8%-18% of animals [41][42][43][44].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…There have also been numerous WGS studies that have examined the genetic diversity of Map from dairy animals (Ahlstrom et al, 2015; Bryant et al, 2016; Ahlstrom et al, 2016; Yue et al, 2016; Leão et al, 2016), but none which have analyzed or addressed mixed Map genotype infections using multiple isolates from a single animal. We recently reported that Map with different s hort s equence r epeat (SSR) types could be isolated from individual dairy animals from the island of Newfoundland (Podder et al, 2015).…”
Section: Introductionmentioning
confidence: 99%